Estimation and Correlation of Serum C-Reactive Protein in Patients with Oral Squamous Cell Carcinoma - Khushali H. Shah; Sima P. Odedra; R V Subramanyam; Vandana S. Shah; Jayasankar P. Pillai; Pratesh N. Dholabhai (Journal of Indian Academy of Oral Medicine and Radiology)
Background: C-reactive protein (CRP) is an early marker of inflammation and disease activity, and is often used as a diagnostic adjunct. Elevated CRP levels have been linked to poor prognosis in esophageal, gastric, and colorectal cancers. This study evaluates the association and correlation of preoperative serum CRP levels with clinicopathological parameters in oral squamous cell carcinoma (OSCC). Objectives: To determine the relationship between elevated CRP levels and histopathologic grading, lymph node metastasis, lesion type, and tobacco habits in OSCC patients. Methods: The study included 50 OSCC patients and 30 healthy controls. Preoperative serum CRP levels were measured using a CRP assessment kit. Clinicopathological correlations were analyzed using the Chi-square and analysis of variance tests, with a significance threshold of P < 0.05. Results: The mean CRP level was 12.75 mg/dL in OSCC patients, which was significantly higher than in controls (P = 0.004). Elevated CRP levels were correlated with lymph node metastasis (P = 0.024), histopathologic grading (P = 0.035), and tobacco habits, including duration (P = 0.025) and frequency (P = 0.022). Conclusions: CRP levels were significantly elevated in OSCC patients compared to healthy controls, demonstrating a strong association with clinicopathological parameters. Elevated CRP may serve as a prognostic biomarker in OSCC.